2010
DOI: 10.1021/ie101093x
|View full text |Cite
|
Sign up to set email alerts
|

NaY Zeolites Catalyze Dehydration of Lactic Acid to Acrylic Acid: Studies on the Effects of Anions in Potassium Salts

Abstract: NaY zeolite catalysts with and without potassium salt modifications were studied with respect to dehydration of lactic acid to acrylic acid. The selectivity for acrylic acid could be dramatically enhanced by modification of the NaY catalysts with potassium salts. The KI-modified NaY catalyst exhibited the best catalytic performance for lactic acid dehydration, over which 97.6% conversion and 67.9% acrylic acid selectivity could be gained at 598 K. Characterizations with TGA, XRD, N2 adsorption, 27Al MAS NMR, X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
143
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(153 citation statements)
references
References 26 publications
7
143
0
3
Order By: Relevance
“…Matsura et al recently reported a high AA yield of about 80 % [19]. Peng et al reported approximately 68 % AA selectivity over Na-Y zeolites modified with potassium salts [20]. Most of this work has been reported on alkali and alkaline earth phosphates [24,25], calcium phosphates (mostly hydroxyapatites) and modified zeolites [26,27].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Matsura et al recently reported a high AA yield of about 80 % [19]. Peng et al reported approximately 68 % AA selectivity over Na-Y zeolites modified with potassium salts [20]. Most of this work has been reported on alkali and alkaline earth phosphates [24,25], calcium phosphates (mostly hydroxyapatites) and modified zeolites [26,27].…”
Section: Introductionmentioning
confidence: 94%
“…Several authors reported in the literature recently on the dehydration of LA to AA over hydroxyapatite (HAp) catalysts [16][17][18][19] and Na-Y zeolites [20][21][22][23]. Ghantani et al prepared various HAp catalysts by changing Ca/P molar ratio at different pHs and reported a maximum of 60 % selectivity towards AA [17].…”
Section: Introductionmentioning
confidence: 99%
“…It can be obtained from lactic acid by selective dehydration. Thus, several catalytic systems are reported in the literature, such as sulfates, zeolites and phosphates 127), 128) . We recently developed a catalytic system efficient in this reaction, for which a patent has just been filed.…”
Section: 4 Lactic Acid Conversionmentioning
confidence: 99%
“…However, AA is rarely obtained selectively from LA because of easy decarbonylation/decarboxylation leading to acetaldehyde (A) and CO x [8][9][10]. High yields of acrylic acid were obtained using modified zeolites [11][12][13][14][15][16] but they suffered from coking and probable hydrothermal instability.…”
Section: Introductionmentioning
confidence: 99%